An Electron Acceptor Challenging Fullerenes for Efficient Polymer Solar Cells. (7th January 2015) - Lin, Yuze; Wang, Jiayu; Zhang, Zhi‐Guo; Bai, Huitao; Li, Yongfang; Zhu, Daoben; Zhan, Xiaowei
<x xml:space="preserve">Abstract</x> A novel non‐fullerene electron acceptor (ITIC) that overcomes some of the shortcomings of fullerene acceptors, for example, weak absorption in the visible spectral region and limited energy‐level variability, is designed and synthesized. Fullerene‐free polymer solar cells (PSCs) based on the ITIC acceptor are demonstrated to exhibit power conversion efficiencies of up to 6.8%, a record for fullerene‐free PSCs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>